Understanding of Future Prescribers About Antimicrobial Resistance and Their Preparedness Towards Antimicrobial Stewardship Activities in Pakistan: Findings and Implications - Hayat, Khezar; Fatima, Noor; Umer, Muhammad Farooq; Khan, Farman Ullah; Khan, Faiz Ullah; Najeeb, Zia ul Rehman; Ghaffari, Muhammad Abuzar; Raza, Syed Qasim; Liu, Wenchen; Chen, Chen; Fang, Yu (Frontiers in Pharmacology, 2022)
Background: Insufficient antimicrobial-related training for physicians during their undergraduate education could have a negative impact on their prescribing. This study explored the understanding of medical students in Pakistan about antibiotics, perception towards resistance, and preparedness for antimicrobial stewardship programs. Methods: An online cross-sectional study was undertaken with final-year medical students using a validated questionnaire from January 2021 to May 2021. Descriptive and inference statistics were applied for data analysis. Results: Of 411 students, only 6.3% had undergone antimicrobial resistance (AMR) training. 16.1% of students believed that antibiotics are effective for viral ailments. More than half of students agreed that AMR is a major healthcare problem in Pakistan (65.9%). Most students viewed poor infection control practices (66.9%), the use of too many broad-spectrum antibiotics (68.4%) for a longer duration (62.8%) with inadequate doses (67.9%) as the causes of AMR. The student’s preparation was insufficient in interpreting microbiological and pathological results (26.3%), selecting the correct antibiotics (22.1%), and awareness of the antibiotic spectrum (20.9%). The median preparedness score showed significant differences with sex (p = 0.049), age (p<0.001), institute type (p=0.014), and family income (p=0.006). Conclusions: Pakistani medical students showed adequate understanding of antibiotics but lack preparedness for several components of ASPs. More steps need to be taken to adequately prepare medical students for AMR and stewardship initiatives.